2012
DOI: 10.1016/j.fuel.2011.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Testing of minerals and industrial by-products as oxygen carriers for chemical-looping combustion in a circulating fluidized-bed 300W laboratory reactor

Abstract: Chemical-looping combustion (CLC) is a promising technology for future energy production with inherent CO 2 separation. One approach is to use minerals or industrial by-products as oxygen carriers to reduce the costs of the process. This study focuses on the investigation of two iron-based oxygen carriers, which were examined under continuous operation in a 300 W laboratory reactor. Ilmenite is an iron-titanium oxide mineral, whereas iron oxide scale (IOS) is obtained as a by-product from the rolling of sheet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 17 publications
2
43
0
Order By: Relevance
“…Leion et al have concluded that such materials are good candidates for converting solid fuels in chemical looping combustion [21] and Xiao et al have reported promising results using an iron ore to convert solid fuels in a fixed-bed reactor under pressurized conditions [26]. Moldenhauer has investigated the mineral ilmenite and an iron-based oxide scale, in a 300 W circulating chemical looping combustion unit fuelled by syngas, to improve the understanding of the lifetime behaviour and other basic characteristics of these oxygen carriers [29].…”
Section: Oxygen Carriersmentioning
confidence: 99%
“…Leion et al have concluded that such materials are good candidates for converting solid fuels in chemical looping combustion [21] and Xiao et al have reported promising results using an iron ore to convert solid fuels in a fixed-bed reactor under pressurized conditions [26]. Moldenhauer has investigated the mineral ilmenite and an iron-based oxide scale, in a 300 W circulating chemical looping combustion unit fuelled by syngas, to improve the understanding of the lifetime behaviour and other basic characteristics of these oxygen carriers [29].…”
Section: Oxygen Carriersmentioning
confidence: 99%
“…Consequently, incomplete combustion of CH 4 occurred in different continuous CLC plants when Fe-based materials were used [21][22][23][24][25][26][27][28]. Among these materials there were synthetic oxygen carriers prepared by different methods [21][22][23], iron-containing minerals [24][25][26][27] and residues [27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Among these materials there were synthetic oxygen carriers prepared by different methods [21][22][23], iron-containing minerals [24][25][26][27] and residues [27][28]. Our research group at Instituto de Carboquímica (ICB-CSIC) has recently developed a highly reactive Fe-based oxygen carrier prepared by the impregnation method [16].…”
Section: Introductionmentioning
confidence: 99%
“…Outlet gases from the air reactor contain N 2 and unreacted oxygen gases. Thus, the primary benefit of CLHG process is combined CO 2 separation and H 2 generation without entailing any direct cost or energy penalty (Adánez et al, 2012;Moldenhauer et al, 2012 Therefore, redox behaviour of an oxygen carrier is a key issue for the use in CLHG process (Adánez et al, 2004;Cho et al, 2004;Hossain et al, 2008;Kang et al, 2010). In our previous study, nickel ferrite (NiFe 2 O 4 ) powder with a single spinel phase demonstrated higher redox behaviour than standard nickel oxide (NiO) and iron oxide (Fe 2 O 3 ) by a thermogravimetric analyzer (TGA).…”
Section: Introductionmentioning
confidence: 99%